2004
DOI: 10.1073/pnas.0306389101
|View full text |Cite
|
Sign up to set email alerts
|

Topical DNA oligonucleotide therapy reduces UV-induced mutations and photocarcinogenesis in hairless mice

Abstract: UV-induced DNA damage gives rise to mutations and skin cancer. We have previously reported that treatment of skin cells in vitro with thymidine dinucleotide (pTT) activates p53 and increases the ability of cells to repair subsequent UV-induced DNA damage by enhancing endogenous DNA repair capacity. Here we show that topical pTT pretreatment enhances the rate of DNA photoproduct removal, decreases UV-induced mutations, and reduces photocarcinogenesis in UV-irradiated hairless WT repair-proficient and Xpc ؉/؊ he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 38 publications
6
76
0
Order By: Relevance
“…24 Sham-irradiated mice had only a background level of mutations (24 Ϯ 0 ϫ 10 Ϫ5 ) as reported previously for this assay. 19,25 And this level increased nearly fivefold (121.5 Ϯ 10 ϫ 10 Ϫ5 ) after a single UV exposure ( Figure 7). Compared with vehicle control, UVinduced mutations in PL-fed-mice were decreased by ϳ25% (121.5 Ϯ 10.05 ϫ 10 Ϫ5 vs. 90.9 Ϯ 10.6 ϫ 10 Ϫ5 , vehicle vs. PL, P Ͻ 0.058) when assessed 2 weeks after the single UV exposure (Figure 7).…”
Section: Polypodium Leucotomos Reduces Mutations In Murine Skin Aftermentioning
confidence: 99%
See 2 more Smart Citations
“…24 Sham-irradiated mice had only a background level of mutations (24 Ϯ 0 ϫ 10 Ϫ5 ) as reported previously for this assay. 19,25 And this level increased nearly fivefold (121.5 Ϯ 10 ϫ 10 Ϫ5 ) after a single UV exposure ( Figure 7). Compared with vehicle control, UVinduced mutations in PL-fed-mice were decreased by ϳ25% (121.5 Ϯ 10.05 ϫ 10 Ϫ5 vs. 90.9 Ϯ 10.6 ϫ 10 Ϫ5 , vehicle vs. PL, P Ͻ 0.058) when assessed 2 weeks after the single UV exposure (Figure 7).…”
Section: Polypodium Leucotomos Reduces Mutations In Murine Skin Aftermentioning
confidence: 99%
“…19 Twenty-five male mice, ages 2 to 3 months, were used in each group. Polypodium Leucotomos (PL) extract was provided by Industrial Farmacé utica Cantabria (Madrid, Spain) as a slightly sweet but otherwise tasteless powder and was given to mice fresh every day with drinking water.…”
Section: Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Eller et al (15) first demonstrated that administration of DNA oligonucleotides induces DNA repair via a p53-dependent mechanism. Accordingly, a recent in vivo study indicated that topical pretreatment with DNA oligonucleotides enhanced the rate of DNA photoproduct removal, decreased UVinduced mutations, and reduced photocarcinogenesis in UV-irradiated mice (16). We recently observed that the immunostimulatory cytokine IL-12 is able to reduce the amount of DNA damage both in vitro and in vivo (17).…”
Section: Il-18mentioning
confidence: 99%
“…* T4 endonuclease: Assayed in patients with xerodermapigmentosum [36,37]. * DNA oligonucleotides: Enhance the cellular response to subsequent UV irradiation,regardless of the existence of previous DNA damage [38].…”
Section: Antioxidantsmentioning
confidence: 99%